Computational Thinking Skills Theorization in The Vocational High School Computer Programming Subject Context - Herlambang, Admaja Dwi; Rachmadi, Aditya (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
The purpose of the study is to compile concepts related to computational thinking skills in the context of computer programming subject. The research design used is data theorization (grounded theory) with open coding and axial coding data analysis techniques. Three types of data collection protocols are used: interview protocols, observation protocols, and recording protocols. The characteristics informants used are students who have experience learning computer programming in the vocational high school. The research produced several concepts, namely the problem concept, which then gave rise to the computational thinking skills concept. The problem concept consists of three sub-concepts: the common problem sub-concept, the medium problem sub-concept, and the high problem sub-concept. The concept of computational thinking skills is a set of skills required in the problem-solving process in computer programming. Computational thinking is not just a thought process but an expression of skills that others can observe. In the computer programming subject context, two concepts influence the process of mastering computational thinking skills: the guidance strategies concept and the information sources concept. The concept of success becomes a mediator in developing computational thinking skills. The theory produced in this study can be used as a basis for conducting research with quantitative designs related to deductive proof of the theory.